Are smartphones a tool to cope with the fear of childbirth? The correlation between the fear of loss of connection and the fear of childbirth - BAYRI BİNGÖL, FADİME (My University, 2024)
OBJECTIVE: With the spread of smartphones, they have become an indispensable part of life, and nomophobia (No-Mobile-Phone Phobia) has emerged. METHODS: The present research is a cross-sectional study and was conducted with 3,870 primiparous pregnant women between April and May 2022. The research data were collected using the Personal Information Form, Nomophobia Questionnaire, and Wijma Delivery Expectancy/Experience Questionnaire. RESULTS: The Wijma Delivery Expectancy/Experience Questionnaire score of the pregnant women who participated in the study was 22.3% (n=863) had a clinical fear of childbirth and 19.5% (n=753) had extreme nomophobia. Considering the correlation of the Nomophobia Questionnaire and Wijma Delivery Expectancy/Experience Questionnaire scores with other variables, it was found that the Wijma Delivery Expectancy/Experience Questionnaire scores increased with the increasing Nomophobia Questionnaire total score (p=0.000, r=236) and the Nomophobia Questionnaire total score and fear of childbirth increased with an increase in the daily phone usage time. It was also revealed that women who had smartphone applications related to fetal development had higher nomophobia levels (p=0.0001), while they had a lower fear of childbirth. CONCLUSION: This study found that one in every five pregnant women was extremely nomophobic and had a clinical fear of childbirth and that nomophobia and the fear of childbirth were correlated at the clinical level. In this regard, women should prefer face-to-face communication rather than smartphones throughout the pregnancy period. KEYWORDS: Phobic disorders. Smartphone. Fear. Childbirth. Women.
Keywords: Sağlık Bilimleri; Health Sciences; Klinik Tıp (Med); Clinical Medicine (Med); Phobic disorders; Smartphone; Fear; Childbirth; Women